New Possibilities in Life with Type 2 Diabetes: Experiences from Participating in a Guided Self-Determination Programme in General Practice - Bjørg Karlsen; Bettina Rasmussen Bruun; Bjørg Oftedal (Nursing Research and Practice)
Research suggests that guided self-determination programmes can support self-management of diabetes by empowering self-determined goal setting and competence building. As most research in this area has focused on people with type 1 diabetes, knowledge is lacking on how adults with type 2 diabetes mellitus experience participation in such programmes. This study reports the modelling phase of a complex intervention design that explored the experiences of adults with type 2 diabetes who participated in a nurse-led guided self-determination programme in general practice and examines how the programme affected patients’ motivation to self-manage diabetes. The qualitative design with semistructured interviews included 9 adults with type 2 diabetes who participated in the programme. Qualitative content analysis was used to analyse the data. The findings indicate that the participants experienced new life possibilities after participating in the programme, which seemed to have a positive influence on their motivation for self-management. Through reflections about how to live with diabetes, the participants reinterpreted their life with diabetes by gradually developing a closer relationship with the disease, moving towards acceptance. The fact that dialogue with the nurses was seen to be on an equal footing helped support the participants to become more self-determined.